PRAISE-QUESTION-POLISH (PQP) TECHNIQUE IN TEACHING WRITING - Indah Rahmalia; Ridianto Ridianto (Ensiklopedia Education Review, 2022)
Writing means the ability of the writers in making, expressing, delivering and sharing the ideas in written form. Due to its difficulties of the skill, the teacher should be creative in applying the effective technique, one of them is praise question polish technique.This research was experimental research. The population was the second grade students of SMP N 1 Kec, Luak. There were seven classes of the second grade students which consisted of 237 students. There were two classes chosen. VIII,2 as the experimental and VIII as control class.Cluster random sampling technique to choose these classes. The experimental class was taught using the Praise-Question-Polish (PQP) technique and control was taught using the usual strategy. The instrument was valid because it has content validity. Researcher used inter -rater to see the reliability of the instrument. To analyze the data, researcher used the t-test formula from Gay and Airasian. The researcher compared the t-calculate and t-table by using a significant level of 0.05 with the degree of freedom/df (). After the researcher got data, it was found that t-count was -0.6524 and t-table was 2.000. from the calculated null hypothesis was accepted. The t-test was smaller than t-table. It meant that the research hypothesis was rejected. In other word, there was not significant effect of using Praise-Question-Polish technique in teaching writing.keywords: writing, teaching writing, Praise-Question-Polish (PQP) Technique